Time to Look Again? Copyright and Freedom of Panorama - Barrett, Jonathan (Victoria University of Wellington Law Review, 2017)
Copyright grants exclusive rights to authors of qualifying works. However, the Copyright Act 1994 permits reproduction, communication and commercial exploitation of certain artistic works which are on permanent public display. This exclusion from copyright, which is widely referred to as "freedom of panorama", is distinguishable from other permitted uses which tend to be narrow in scope and commonly manifest an element of fair dealing. Like other corresponding provisions of British heritage copyright legislation, New Zealand's freedom of panorama exclusion is significantly wider than comparable permitted uses in other jurisdictions. This article examines freedom of panorama in New Zealand. Note is taken of the Waitangi Tribunal report Wai 262, which considered among other issues the protection of Māori cultural treasures within the intellectual property law system. As points of comparison, selected overseas approaches to freedom of panorama are outlined. This article questions whether the current exclusion strikes an appropriate balance between competing rights and interests.